Vom Staat zum Markt. Privatisierung aus politikwissenschaftlicher Perspektive. - Sack, Detlef (Springer VS, 2019)
Privatisierung ist keine wirtschaftliche Notwendigkeit, sondern das Ergebnis von Politik. Das Lehrbuch führt in die international vergleichende politikwissenschaftliche Privatisierungsforschung ein. Es stellt grundlegende Definitionen, Konzepte und Theorien vor, mit denen Entstaatlichung im öffentlichen Sektor untersucht wird. Insgesamt thematisiert der Band die (machtpolitischen) Gründe für Privatisierung wie die Effekte der Entstaatlichung, die begleitende Regulierung und die demokratischen Konsequenzen.

The author addresses persistent research gaps in urban climate governance and North-South cooperation. He compares the form, processes and outcomes of four local climate protection projects conducted as part of German-Indian urban cooperation and explores the conditions associated with the success and/or failure in these initiatives. The study concludes that North-South city partnerships struggle to fully realise their potential to foster global climate protection efforts, specifically in terms of post-project sustainability, multi-level governance coordination, and mutuality. On the basis of these findings, practical policy recommendations on how to maximise the outcomes and broaden the scope of urban climate cooperation are provided.
Keywords: Institutionengeschichte; Privatisierung; Entstaatlichung; Politikwissenschaft; Demokratie; Regulierung; Vergleich